MODEL DAN STRATEGI PEMBELAJARAN ANAK ADHD ( Attention Deficit Hyperactivity Disorder) - Abdul Rosyad; Naf’an Tarihoran (Journal of Innovation Research and Knowledge, 2022)
This study will discuss how the model and learning strategies of ADHD children are. This research is a qualitative research with a psychological-pedagogic approach. Data analysis of the data was carried out with a descriptive type of analysis by checking the validity of the data by means of triangulation of the data. The results of the study reveal that the learning models that can be used for ADHD children include the inclusive learning model, the PAKEM learning model, the contextual learning model and the cooperative learning model. While the strategies that can be used to help ADHD children who have attention problems, difficulties in impulsivity and hyperactivity are different from one another, in principle the strategies can be done in two ways, namely class-based strategies and individual strategies.